Prevalence of depression among children living in orphanage - Ramagopal, Ganavi; Narasimhan, Shobana; Devi, L. Uma (International Journal of Contemporary Pediatrics, 2016)
Background:The children who are placed in orphanages especially during very young age, for long duration are found to be at increased risk of developing psychiatric problems like depression, behavioural and emotional disorders later in life. The objective of the study was to assess the prevalence and severity of depression among children living in orphanage. Methods: A cross sectional descriptive study, involving 180 children in the age group of 12-18 years living in orphanage was conducted. After obtaining permission and informed consent, demographic details were noted and hamilton depression scale was administered to assess depression. Scoring was done, severity of depression was classified and results were tabulated. Results:53% were age group of 12-14 years and 46% were 15-17 years, 52% females and 48% males, 35% had depression, most of them who had depression were in the age group of 15-17 years and majority were females. According to severity of depression 52% had mild depression, 23% had moderate depression, 14% had severe depression, 9% had very severe depression and 38% of depressed children had suicidal intentions. Conclusions:Depression is one of the most common psychiatric disorder prevalent among children living in orphanages especially adolescent females so early identification and intervention is necessary for the children living orphanages to prevent further consequences.